Cost accounting for additive manufacturing - Yu, Dehui (2018)
Additive Manufacturing(AM), or else widely known as three-dimensional (3D) printing, is an innovative technology that can build 3D products by adding material layer upon layer according to computer-aided design(CAD) models. This technology overcomes many limitations of current manufacturing methods and can produce intricate products quite fast. Currently, AM is used in various applications, such as medical, aerospace and automotive industry. However, despite the rapid technological advancement of Additive Manufacturing, its large-scale adoption in industry is still lagging. Part of the reason is due to lack of understanding of the real cost of additive manufacturing relative to conventional manufacturing methods, as well as the detailed configuration of the whole supply chain. Due to the implementation of AM, several manufacturing techniques will be replaced, and the process structure will also be influenced. The objective of this project is to analyze the lifecycle costing structure of Additive Manufacturing. Major cost elements of AM were identified and their effects on the total cost were quantitatively evaluated. A mathematical model of the AM costing was established and implemented within a spreadsheet-based software. In addition, a case study based on an aerospace part was conducted to illustrate the application of the cost model. With this model, major barriers for additive manufacturing adoption can be identified, and companies are able to make a more informed decision when comparing additive manufacturing against conventional manufacturing methods.